2014
DOI: 10.5558/tfc2014-015
|View full text |Cite
|
Sign up to set email alerts
|

Growth dynamics of successive post-fire cohorts of black spruce: Is site potential reduced?

Abstract: Black spruce is one of the main commercial species in boreal forests of North America. It usually forms large and single-species natural stands in eastern Canada, yet in recent years, parts of this area have undergone forest cover regression and the conversion of closed-crown forests to open lichen woodlands, partly due to successive disturbances and regeneration accidents. We studied two successive post-fire cohorts growing at the same site, for which a clear forest cover regression trajectory has already bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…action potential to increase productivity. As a result, plans to afforest dry northern woodlands with jack pine, known for its generally more rapid growth and higher resilience to fire compared with black spruce, may need to be considered with caution (Rapanoela et al 2015), even if preliminary studies have shown some early successes (Tremblay et al 2013;Hébert et al 2014;Côté et al 2014).…”
Section: Findings and Implicationsmentioning
confidence: 99%
“…action potential to increase productivity. As a result, plans to afforest dry northern woodlands with jack pine, known for its generally more rapid growth and higher resilience to fire compared with black spruce, may need to be considered with caution (Rapanoela et al 2015), even if preliminary studies have shown some early successes (Tremblay et al 2013;Hébert et al 2014;Côté et al 2014).…”
Section: Findings and Implicationsmentioning
confidence: 99%
“…Those examining naturogenic processes would include studies quantifying the effects of edaphic variation [1], resource competition [2], abiotic wind stress [3], insect defoliation [4], drought [5], and pathogens [6,7] on tree growth, whereas anthropogenic based investigations would include studies assessing tree growth responses to intensive forest management treatments, such as pre-commercial thinning [8] and commercial thinning [9], atmospheric pollution [10], and global warming [11]. Stem analysis has also been an essential tool for reconstructing ecological disturbance histories (e.g., [12][13][14]) and past climate variability within forest ecosystems (e.g., [15,16]). Furthermore, tree ring sequences have been used as terrestrial-based proxies in reconstructing past continental-scale temperatures and hydroclimatic changes in order to detect anthropogenic-generated climate change and quantifying the associated effects (e.g., [17,18]).…”
Section: Introductionmentioning
confidence: 99%